Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1172/jci29383
|View full text |Cite
|
Sign up to set email alerts
|

Secreted PCSK9 decreases the number of LDL receptors in hepatocytes and inlivers of parabiotic mice

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a member of the proteinase K subfamily of subtilases that reduces the number of LDL receptors (LDLRs) in liver through an undefined posttranscriptional mechanism. We show that purified PCSK9 added to the medium of HepG2 cells reduces the number of cellsurface LDLRs in a dose-and time-dependent manner. This activity was approximately 10-fold greater for a gain-of-function mutant, PCSK9(D374Y), that causes hypercholesterolemia. Binding and uptake of PCSK9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
591
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(654 citation statements)
references
References 36 publications
40
591
5
Order By: Relevance
“…Recent studies show that the self-cleaved form of PCSK9 binds directly to the LDLR [28]. Biochemical studies using recombinant proteins have revealed that the first EGF-like repeat of the LDLR (EGF-A) suffices for binding of recombinant, purified PCSK9, and that binding to this repeat is calcium dependent [26].…”
Section: Pcsk9 Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that the self-cleaved form of PCSK9 binds directly to the LDLR [28]. Biochemical studies using recombinant proteins have revealed that the first EGF-like repeat of the LDLR (EGF-A) suffices for binding of recombinant, purified PCSK9, and that binding to this repeat is calcium dependent [26].…”
Section: Pcsk9 Structurementioning
confidence: 99%
“…Additionally, the affinity of PCSK9 for the receptor is enhanced at endosomal pH [26,29]. Moreover, mutations associated with PCSK9 gain of function result in enhanced LDLR clearance from the cell surface [28,30], and at least one mutant, D374Y, exhibits ~25-fold increased affinity for the receptor at neutral pH [28,29]. However, it is still not clear whether the latent proteolytic activity of the enzyme is required for receptor downmodulation.…”
Section: Pcsk9 Structurementioning
confidence: 99%
“…On the surface of hepatocytes, PCSK9 binds to the LDLR, forming a complex that is internalized and directs LDLR for intracellular degradation. 11 It should be noted that PCSK9 acts as a chaperone to facilitate intracellular degradation of LDLR, and that this role is independent of its enzymatic activity. 12,13 By promoting LDLR degradation, PCSK9 prevents recycling of LDLR to the cell membrane, leading to a post-translational reduction in LDLR expression.…”
mentioning
confidence: 99%
“…Specifically, a concentration‐dependent impact of PCSK9 on liver cell CD81 expression has been documented 16, 17. Also, circulating PCSK9 down‐regulates LDLR expression on the hepatocyte surface, thus decreasing LDL catabolism and increasing plasma LDL‐cholesterol (LDL‐C) levels 18, 19. Although there is evidence that PCSK9 decreases VLDLR expression in adipose tissue 20, whether such a down‐regulation may occur in the liver is not established and the potential impact of PCSK9‐mediated change in VLDLR expression on HCV infection is still unknown.…”
Section: Introductionmentioning
confidence: 99%